Screening Preeclampsia and the Role of Low Dose Aspirin for the Prevention of Preeclampsia - Putra, Wayan Artana (Open Access Macedonian Journal of Medical Sciences, 2023)
Preeclampsia is one of the leading causes of maternal morbidity and can affect fetal conditions such as inhibition of intrauterine growth, premature labor, placental abruption, fetal distress, and, worst of all, intrauterine fetal death. In contrast to the decreasing incidence of pregnancies with infection, preeclampsia did not decrease significantly during the past two decades. Prevention of preeclampsia is an effort that is currently being intensively carried out to reduce morbidity and mortality of pregnant women. Prophylactic administration of low-dose aspirin (81 mg/day) is recommended in women with a high risk of preeclampsia. It should be started between 12 weeks of gestation to 18 weeks (optimal before 16 weeks). Aspirin has been shown to be safe for the mother and the fetus during pregnancy. Treatment with aspirin also did not increase the risk of developing congenital malformations and had no adverse effect on fetal development or bleeding complications during the neonatal period.